Efficient Resource Utilization in Information Security Risk Management Investment - Nyapete, Mitende Nicholus; Rodrigues, Anthony J.; Liyala, Samuel (International Journal of Computer Applications Technology and Research, 2018)
Efficient Resource Utilization in Information Security Risk Management Investment can improve organization resiliency to information security threats through identifying key information assets and security risks so that information security expenditures can be directed cost effectively. The purpose of this study is to determine if framing and evaluation components of prospect theory informs information security investment decisions. An empirical study was conducted on six microfinance enterprises using Cochran’s correctional formula. Mediation Regression Analysis (MRA)was used to determine the impact of organization and human factors on efficient information security risk management investment. The study established that Rational Choice Decision Models(RCDM) in the context of information security investment needs to be supplemented with risk perception measurement and account for individual level decision biases.
Keywords: Information Security Risk Management Investment; Rational Choice Decision Models; Information security; Prospect Theory; Information Security; Efficient